Optimization of BaxSr1-xCo0.9Nb0.1O3-8 perovskite as oxygen semi-permeable membranes by compositional tailoring - Zhao, J.; Zhang, K.; Gao, D.; Shao, Zongping; Liu, Shaomin (Elsevier Science Ltd, 2010)
Mixed conducting SrCo0.9Nb0.1O3−δ perovskite is a newly developed promising ceramic membrane material for air separation. In this work, SrCo0.9Nb0.1O3−δ was further optimized by the introduction of Ba to partially replace Sr in the A-site of the perovskite structure. The phase structure, phase stability, carbonate formation rate under carbon dioxide atmosphere, electrical conductivity, oxygen desorption properties, and oxygen permeation properties of BaxSr1−xCo0.9Nb0.1O3−δ (BSCNx) with varying Ba2+ doping level were systematically investigated. Pure phase cubic perovskite was formed at x = 0.0–0.8. BSCNx (x = 0.0–0.8) can be stably operated in atmospheres with oxygen partial pressure varying from at least 1 atm to as low as 10−5 atm (Ar atmosphere). The barium doping concentration had a significant effect on electrical conductivity and oxygen permeability of the membranes. BSCN0.6 had the highest oxygen permeation flux of 2.67 × 10−6 mol cm−2 s−1 for 0.87 mm thickness at 900 °C and the highest oxygen ionic conductivity of 1.38 S cm−1 at 900 °C.